Iatrogenic Hepatic Portal Venous Gas in a Patient With Crohn's Disease After Colonoscopy - Mubarik, Ateeq (ACG Case Rep J, 2019)
Hepatic portal venous gas is a radiologic sign and is associated with several abdominal disorders. The prognosis and survival of the patient depends on the underlying etiology. Most cases respond to broad-spectrum antibiotics, but some may need surgical intervention. We report a case of hepatic portal venous gas after colonoscopy in a patient with Crohn's disease.